Elective hospital admissions: secondary data analysis and modelling with an emphasis on policies to moderate growth - Martin Chalkley; Barry McCormick; Robert Anderson; Maria Jose Aragon; Nazma Nessa; Catia Nicodemo; Stuart Redding; Raphael Wittenberg (National Institute for Health Research, 2017)
Background: The English NHS faces financial pressures that may render the growth rates of elective admissions seen between 2001/2 and 2011/12 unsustainable. A better understanding of admissions growth, and the influence of policy, are needed to minimise the impact on health gain for patients. Objectives: This project had several objectives: (1) to better understand the determinants of elective activity and policy to moderate growth at minimum health loss for patients; (2) to build a rich data set integrating health, practice and local area data to study general practitioner (GP) referrals and resulting admissions; (3) to predict patients whose treatment is unlikely to be cost-effective using patient-reported outcomes and to examine variation in provider performance; and (4) to study how policies that aim to reduce elective admissions may change demand for emergency care. The main drivers of elective admissions growth have increased either supply of or demand for care, and could include, for example, technical innovations or increased awareness of treatment benefits. Of the factors studied, neither system reform nor population ageing appears to be a key driver. The introduction of the prospective payment tariff 'Payment by Results' appears to have led to primary care trusts (PCTs) having increasingly similar lengths of stay. In deprived areas, increasing GP supply appears to moderate elective admissions. Reducing the incidence of single-handed practices tends to reduce referrals and admissions. Policies to reduce referrals are likely to reduce admissions but treatments may be particularly reduced in the lowest referring practices, in which resulting health loss may be greatest. In this model, per full-time equivalent, female and highly experienced GPs identify more patients admitted by specialists. Results: It appears from our studies that some patient characteristics are associated with not achieving sufficient patient gain to warrant cost-effective treatment. The introduction of independent sector treatment centres is estimated to have caused an increase in emergency activity rates at local PCTs. The explanations offered for increasing elective admissions indicate that they are manageable by health policy. Conclusions: Further work is required to understand some of the results identified, such as whether or not high-volume Clinical Commissioning Groups are fulfilling unmet need; why some practices refer at low rates relative to admissions; why the period effect, which results from factors that equally affect all in the study at a point in time, dominates in the age-period-cohort analysis; and exactly how the emergency and elective sections of hospital treatment interact. This project relies on the analysis of secondary data. This type of research does not easily facilitate the important input of clinical experts or service users. It would be beneficial if other methods, including surveys and consultation with key stakeholders, could be incorporated into future research now that we have uncovered important questions. Funding: The National Institute for Health Research Health Services and Delivery Research programme.